Adsorption kinetics of propane and propylene in Zeolite 5A-K. Unusual irreversible adsorption of propylene (Superficies y Vacío, 2012)
This study reveals some interesting interactions among olefin-olefin molecules adsorbed onto the solid 5A-K at temperatures below the critic temperature. The irreversible adsorbed propylene molecules act as “active sites” for a second adsorption. The kinetic measurements of pure hydrocarbons were carried out at different temperatures using a glass high vacuum volumetric system. It was found that the adsorption process for propylene was of the activated type, whereas the adsorption uptake for propane was low and completely reversible. The obtained results allow the assumption that the 5A-K sample could be an excellent adsorbent for the separation of C3H6/C3H8 mixtures at 150º C.